Are Charter Schools Safer in Deindustrialized Cities With High Rates of Crime? Testing Hypotheses in Detroit. (August 2017) - Hamlin, Daniel
Families in deindustrialized cities with high crime rates report prioritizing school safety when opting for charter schools. Yet, very little research has investigated whether charter schools are safer than traditional public schools. This study compares charter and traditional public schools in Detroit, Michigan, on perceived school safety by linking student surveys to data on school, neighborhood, and parent-related characteristics. Charter schools exhibited higher perceived school safety than traditional public schools. However, controls for student commute distance and parental involvement largely diminished this difference. Neighborhood charter schools were an exception, maintaining higher perceived school safety net of controls. Overall results suggest that differences in perceived school safety between schools become less prominent after the attributes of school choosers are considered.